Social Cognition and Schizophrenia: Unresolved Issues and New Challenges in a Maturing Field of Research - Vaskinn, Anja (Schizophr Bull, 2020)
Social cognition has become a topic of widespread interest in experimental and treatment research in schizophrenia over the past 15 years. This explosion of interest largely reflects the robust evidence that social cognition is among the strongest known correlates of poor community functioning throughout the course of schizophrenia. While progress has been impressive, we consider several fundamental questions about the scope, structure, and optimal measurement of social cognition that remain unanswered and point to the need for continued method development. We also consider more recently emerging questions about individual differences, ecological and cross-cultural validity, and intervention approaches, as well as broader technological changes that impact how we understand and use social cognition at a societal level. Continued efforts to creatively grapple with the complexities and challenges the field now faces hold great promise for helping us understand and more effectively treat a major source of functional disability in schizophrenia.